Sosialisasi Layanan Transportasi Umum Trans Banyumas Program Buy the Service Kementerian Perhubungan di Kabupaten Banyumas - April Kurniawan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Buy The Service (BTS) Trans Banyumas program is a government initiative aimed at providing a modern, efficient, and technology-based public transportation service in Banyumas Regency. To enhance public understanding of this service, various socialization programs have been conducted by PT Banyumas Raya Transportasi in collaboration with the Banyumas Regency Transportation Agency and relevant stakeholders. These socialization programs include Trans Banyumas Goes To School, Edutrans, community outreach, television broadcasts, and public information booths. Each program is designed to reach various community groups, particularly students, who constitute the dominant users of this public transportation service. Through presentations, discussions, field practice, and mass media utilization, the public is informed about the cashless payment system, service routes, operational schedules, and the benefits of public transportation in improving mobility efficiency. The results of these socialization efforts indicate an increase in public awareness of the BTS Trans Banyumas service, although passenger numbers remain fluctuating, especially during school holidays. Therefore, additional strategies are needed to attract more users from the working population and the general public to ensure the optimal and sustainable utilization of this service.